The Metric Dimension of Algebraic Constructed Graph of Dihedral Group Dn - Qammar Rubab; Saba Rao; Muhammad Ishtiaq (Scientific Annals of Computer Science)
In this article, we discusses the concept of metric dimension in graph theory and its applications in various scientific fields. Metric dimension is the minimum number of vertices in a graph that can uniquely identify all other vertices based on their distances to the vertices in the set. It has applications in computer science, chemistry, and engineering. We focuses on the study of a specific class of graphs called the algebraic constructed graph of dihedral groups denoted by Dn. The study aims to calculate the resolving sets and metric dimension of these graphs.